Comparing trends of perinatal mortality in two rural areas of Matlab, Bangladesh. Issue 1 (6th April 2020) - Rahman, Aminur; Austin, Anne; Anwar, Iqbal; Taneepanichskul, Surasak
Abstract : Purpose: Sixteen million adolescents give birth each year, constituting 11% of all births worldwide. Adverse adolescent pregnancy outcomes are well-documented. Available data on adolescent pregnancies have mainly relied on self-reported age and retrospective survey data, which might not capture adolescent births accurately. This paper reports on trends in adolescent pregnancy and associated adverse birth outcomes in Matlab, Bangladesh, using data from the Matlab Heath and Demographic System (HDSS) which precisely documents maternal age. Design/methodology/approach: The study was conducted in the rural subdistrict of Matlab in Bangladesh. HDSS data were used to examine trends in adolescent motherhood (10–19 years) in the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr, b) service areas (ISA) and government service areas (GSA) between 2007 and 2015. A total of 4, 996 adolescent mothers were included in the analysis. Chi-square testing and binary logistic regression were used to document adolescent pregnancy trends and the differences in and causes of perinatal death. Findings: The fertility rate was 27 per 1000 adolescent mothers in ISA and 20 per 1000 adolescent mothers in GSA, during the 9 years of the study period. The adjusted odd of an adolescent mother having a perinatal death in ISA, relative to GSA was 0.69. Significant determinants of perinatal death among adolescent mothers included maternal education, paternal education, mother's age at first birth, asset score and distance from the nearest health facility. Originality/value: This paper documents the real trend of adolescent pregnancy by capturing the accurate age at pregnancy for the first time in Bangladesh.